STUDI KELAYAKAN AIR IRIGASI BENDALI KAMPUNG MIMI BARU DISTRIK JAGEBOB KABUPATEN MERAUKE - Irba Djaja; Daud Pasalli (Universitas Musamus, Merauke, Papua, 2012)
Long Storage is one of place of water supplies to provides water for the societies needs, the same as long storage at Mimi Baru village in Jagebob District. That long storage was built to fulfill the societies water need especially for agriculture`s irrigation needs. But infact the usenes of water in long storage is not optimal yet. Survey of the long storage`s water profiency in Mimi Baru Village Jagebob District purposed that the water in this long storage can be used maximalize by the societies there, especially farming needs. The methodology used by the writer in this research is literature study and also field study where the writer colleted datas related with the tittle of the writing and than making an analysis how to get the profit water which can be used for the agriculture`s irrigation. Based on the counted of long storage volum that the total capacity of water is 74.100 m3 with the maximal capacity is 180.975 m3. This capacity in enough or qualified for agriculture’s irrigation with the total width 27,22 hectares, because the water needs for irrigation technicaly is 0,102 lt/second or 8.797,594 ltr/days. While, based on the laboratory tested which was done by the PU Instance of Papua Province was recomendated that the water in this long storge is save to be ued for agriculture`s irrigation, because the chemist unsures in that are stil in save level for agriculture and harmless for the plants.